Supplementing organic-complexed or inorganic Co, Cu, Mn, and Zn to beef cows during gestation: postweaning responses of offspring reared as replacement heifers or feeder cattle - Harvey, Kelsey M.; Cooke, Reinaldo F.; Colombo, Eduardo A.; Rett, Bruna [UNESP]; de Sousa, Osvaldo A. [UNESP]; Harvey, Lorin M.; Russell, Jason R.; Pohler, Ky G.; Brandão, Alice P. (Oxford University Press (OUP), 2021)
One hundred and ninety nonlactating, pregnant beef cows (¾ Bos taurus and ¼ Bos indicus; 138 multiparous and 52 primiparous) were assigned to this experiment at 117 ± 2.2 d of gestation (day 0). Cows were ranked by parity, pregnancy type (artificial insemination = 102, natural service = 88), body weight (BW) and body condition score, and assigned to receive a supplement containing: (1) sulfate sources of Cu, Co, Mn, and Zn (INR; n = 95) or (2) an organic complexed source of Cu, Mn, Co, and Zn (AAC; Availa4; Zinpro Corporation, Eden Prairie, MN; n = 95). The INR and AAC provided the same daily amount of Cu, Co, Mn, and Zn, based on 7 g of the AAC source. From day 0 to calving, cows were maintained in a single pasture and segregated 3 times weekly into 1 of 24 individual feeding pens to receive treatments. Calves were weaned on day 367 (200 ± 2 d of age), managed as a single group for a 45-d preconditioning period (days 367 to 412), and transferred to a single oat (Avena sativa L.) pasture on day 412. Heifer calves were moved to an adjacent oat pasture on day 437, where they remained until day 620. Heifer puberty status was verified weekly (days 437 to 619) based on plasma progesterone concentrations. Steer calves were shipped to a commercial feedlot on day 493, where they were managed as a single group until slaughter (day 724). Plasma cortisol concentration was greater (P = 0.05) in AAC calves at weaning but tended to be less (P = 0.10) on day 370 compared with INR calves. Mean plasma haptoglobin concentration was greater (P = 0.03) in INR vs. AAC calves during preconditioning, and no treatment effects were noted (P = 0.76) for preconditioning average daily gain (ADG). Puberty attainment was hastened in AAC heifers during the experiment (treatment × day; P < 0.01), despite similar (P = 0.39) ADG between treatments from days 412 to 620. Expression of myogenin mRNA in the longissimus muscle was greater (P = 0.05) in INR vs. AAC heifers on day 584. No treatment effects were detected (P ≥ 0.24) for steer ADG from day 412 until slaughter, nor for carcass quality traits. Hepatic mRNA expression of metallothionein 1A was greater (P = 0.02) in INR vs. AAC steers on day 586. In summary, supplementing Co, Cu, Zn, and Mn as organic complexed instead of sulfate sources to beef cows during the last 5 mo of gestation did not improve performance and physiological responses of the steer progeny until slaughter, but hastened puberty attainment in the female progeny reared as replacement heifers.
Keywords: beef cows; gestation; offspring; physiology; production; trace minerals